Model-based safety analysis of software product lines. (2016) - Oliveira, André Luiz De; Braga, Rosana T.V.; Masiero, Paulo Cesar; Papadopoulos, Yiannis; Habli, Ibrahim; Kelly, Tim
Software product lines (SPLs) provide an engineering basis for the systematic reuse of artefacts used for development, assessment, and management of critical embedded systems. Hazards and their causes are safety properties that may change according to the selection of variants in a particular SPL product. Therefore, safety analysis assets such as fault trees and failure modes and effects analysis (FMEA) cannot be directly reused because they are dependent upon the selection of product variants. In this paper, model-based safety analysis techniques and SPL variability management tools are used together to reduce the effort of product safety analysis by: reusing SPL hazard analysis, and providing automatic safety analysis for each SPL product. The benefit of applying the approach is the reduction of effort to perform product safety analysis. The proposed approach is illustrated using the Hephaestus variability management tool and the HiP-HOPS model-based safety analysis tool to generate fault trees, and FMEA for products of an automotive hybrid braking system SPL. The safety assessment artefacts generated by the approach provide feedback for the SPL development process helping safety engineers to make decisions earlier in the development lifecycle.